LBX2-AS1 as a Novel Diagnostic Biomarker and Therapeutic Target Facilitates Multiple Myeloma Progression by Enhancing mRNA Stability of LBX2 - Jia, Haipeng; Liu, Yan; Lv, Sulong; Qiao, Ruifang; Zhang, Xiaofen; Niu, Fei; Shang, Wenqing; Liu, Shumei; Dong, Jing; Zhang, Zhirong (Frontiers in Molecular Biosciences, 2021)
Objective: Multiple myeloma (MM) represents a common age-associated malignancy globally. The function and underlying mechanism of antisense lncRNA LBX2-AS1 remain ambiguous in multiple myeloma (MM). Herein, we aimed to observe the biological implication of this lncRNA in MM. Methods: RT-qPCR was employed to examine circulating LBX2-AS1 and LBX2 in 60 paired MM and healthy subjects. Correlation between the two was analyzed by Pearson test. Under transfection with shLBX2-AS1, proliferation and apoptosis were evaluated in MM cells through CCK-8, colony formation and flow cytometry. LBX2 expression was examined in MM cells with shLBX2-AS1 or pcDNA3.1-LBX2 transfection. Following treatment with cycloheximide or actinomycin D, LBX2 expression was examined in pcDNA3.1-LBX2-transfected MM cells at different time points. Rescue assays were then presented. Finally, xenograft tumor models were established. Results: Circulating LBX2-AS1 was up-regulated in MM patients and positively correlated to LBX2 expression. Area under the curve (AUC) of LBX2-AS1 expression was 0.7525. Its up-regulation was also found in MM cells and primarily distributed in cytoplasm. LBX2-AS1 knockdown distinctly weakened proliferative ability and induced apoptosis in MM cells. Overexpressing LBX2-AS1 markedly strengthened LBX2 expression by increasing its mRNA stability. Rescue assays showed that silencing LBX2-AS1 distinctly weakened the pcDNA3.1-LBX2-induced increase in proliferation and decrease in apoptosis for MM cells. Silencing LBX2-AS1 markedly weakened tumor growth. Conclusion: Our data demonstrated that circulating LBX2-AS1 could be an underlying diagnostic marker in MM. Targeting LBX2-AS1 suppressed tumor progression by affecting mRNA stability of LBX2 in MM. Hence, LBX2-AS1 could be a novel therapeutic marker against MM.